Monetary policy, long real yields and the financial crisis - Laura Moretti (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
This paper investigates the role of monetary policy in the collapse in the long-term real interest rates in the decade before the onset of the financial crisis using a sample of five advanced economies (United States, United Kingdom, the euro area, Sweden and Canada). The results from an estimated panel VAR with monthly data show that, while monetary policy shocks had negligible effects on long-term real interest rates, shocks to the long-term real interest rates had a one-to-one effect on the short nominal rate.
Keywords: E43; E52; E58; 330; monetary policy; long-term real interest rates; panel VAR